Effect of air-drying time on dentin shear bond strength of a total-etch and a self-etch adhesive - Belen, Willard B.
Composite restorations are popular due to increasing patients' esthetic demands and enhancements in composition of adhesive resins have resulted in improved clinical performance. Two of the widely used adhesive systems of today are the total-etch (TE) and self-etch (SE) adhesive systems. Different factors affect dentin bond strength including light irradiation, cyclic loading, elevated temperature and humidity, dentin substrate, dentin surface moisture, adhesive film thickness and air-drying time. A fes studies have shown that air-drying time affects bond strength. However, very few manufacturers indicate the appropriate air-drying time of their products. this study was undertaken to determine the effect of primer air-drying time on dentin shear bond strength (SBS) of a total-etch and a self-etch adhesive system. Solobond M (SM), a TE adhesive, and FL-Bond (FL-B), an SE adhesive, with their corresponding composites, Admira and Beautiful, were used respectively. Sixty bovine incisor teeth were randomly divided into 6 groups (n=10). The bonding surfaces were prepared using a 600-grit SiC paper and then ultrasonically cleaned. A 3.0 mm diameter hollow plastic tube with height of 5.0 mm was used to define the bonding area. The adhesive systems were then applied according to manufacturer's instructions and the primer was exposed to three air-drying times (0,5 and 10 seconds) followed by packing of composite resin. The specimens were stored in a water bath at 37°C for 42 hours prior to testing. SBS was then determined using an Instron Univrersal Testing Machine with a crosshead speed of 1.0 mm/min. Statistical analysis using 2-way ANOVA showed that there is no significant relationship between air-drying time and SBS within each brand of adhesive system (p=0.445> α = 0.05). The results also showed that there is a significant difference in the SBS between the two brands of adhesive systems (p = 0.000 < α = 0.05). Therefore, the researches concluded that (1) for both brands, primer air-drying time has no significant effect on SBS to dentin, and (2) the mean SBS to dentin of SM is significantly higher than the mean SBS to dentin of FL-B.